A (in)eficácia do atendimento protetivo individual da DPE-RS em garantir o acesso à justiça à população vulnerável - Girelli, Louis Balbinote (2024)
This research will analyze the performance of the Public Defender's Office of the State of Rio Grande do Sul (DPE-RS) as a guarantor of access to justice for the vulnerable population, from the perspective of individual protective care. The question that permeates the research is whether individual protective care, made available to vulnerable people by DPE-RS, is effective in guaranteeing access to justice. The objective is to conceptualize the principle of access to justice and its “waves”, as well as to historically contextualize the Public Defender's Office in Brazil and its development to, in the end, delve deeper into the nuances of vulnerability and individual protective care as a means of access to justice. Judicial power. The relevance of the research is justified considering the increase in vulnerability in Brazil resulting from the COVID-19 pandemic and the effectiveness of the public sector in supporting it. Finally, it is concluded that individual protective care, in itself, is not effective in guaranteeing access to justice for those in vulnerable situations.